JITTER OPTIMIZATION WITH MOBILE NODE BATCH VERIFICATION - Jagadeesha R , Thippeswamy K (International Journal of Advanced Science and Technology, 2020)
Jitter occurs in transferring signed multicast batches are identified by calculating the average round trip time in transferring the sequence of ping packets with time stamp for small periodicity. If the average round trip time between two sequences of ping packets is well under the acceptable threshold limit than the periodicity of the ping packet sequence is doubled. If the average round trip time between two recent sequences of ping packet transmission is more than acceptable values, then the inter-frame delay and Buffer size are calculated by considering the average delay of two recent sequences and the number of data packets coming at that time. A batch RSA signature is verified to check for authenticity and the Inter-frame delay is applied between data packets. The inter-frame delay does not allow contents to display with the variable delay between data packets. This method is suitable for mobile receivers where multicast data streaming with the small delay is tolerable and data lose intolerant applications.